Numerical investigation of dynamics of unsteady sheet/cloud cavitating flow using a compressible fluid model - Chen, Guang-Hao; Wang, Guo-Yu; Huang, Biao; Hu, Chang-Li; Wang, Zhi-Ying; Wang, Jian (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2015)
In this paper, a compressible fluid model is proposed to investigate dynamics of the turbulent cavitating flow over a Clark-Y hydrofoil. The numerical simulation is based on the homogeneous mixture approach coupled with filter-based density correction model (FBDCM) turbulence model and Zwart cavitation model. Considering the compressibility effect, the equation of state of each phase is introduced into the numerical model. The results show that the predicted results agree well with experimental data concerning the time-averaged lift/drag coefficient and shedding frequency. The quasi-periodic evolution of sheet/cloud cavitation and the resulting lift and drag are discussed in detail. Especially, the present compressible-mixture numerical model is capable of simulating the shock waves in the final stage of cavity collapse. It is found that the shock waves may cause the transient significant increase and decrease in lift and drag if the cavity collapses near the foil surface.